THE ELEMENTS OF PACKAGING THAT FORM A BRAND PERSONALITY. A CASE STUDY ON AROMA PREMIUM SEKOTENG PRODUCTS - Teofilus Teofilus; Timotius FCW Sutrisno; Angeline Gomuljo (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
A trend to a heatlhier lifestyle triggers a shift in consumer’s behavior to consume healthy foods and to avoids any preservatives. Several companies in Indonesia began to contribute to this trend including UD Maju Jaya who also contributing onto this trend by producing products called premium sekoteng AROMA. The problem occured when the company experienced a sales decline as 93,4% in traditional market distribution channel and 39,4% in modern distribution channel because the product itself did not show the element of a packaging that could attract consumers to purchase since a brand personality from a packaging itself should form a bond on consumer’s thoughts and feelings unto the brand. Therefore, the purpose of this study is to determine the effect of packaging elements through brand personality on premium sekoteng AROMA. This study uses a quantitative approach. In this study, data collection was done by distributing questionnaires using a purposive sampling technique with the conditions as the population must be B2B consumers who had purchased and consumed premium sekoteng AROMA. The results showed that functionality packaging and packaging saleability significantly have a tendency to influence brand personality